Where Next for UK Financial Services Post Brexit? - Hall, Sarah (Border Crossing, 2025)
Despite being a central component of the UK’s political economy financial services were largely omitted from the Trade and Cooperation Agreement (2021) struck after the UK left the EU. Whilst worst scenarios in terms of the implications of this for the sector have not materialised, there are growing concerns that the sector is flatlining. In response, and as part of a wider ‘reset’ in UK-EU relations, the Labour government elected in 2024 has sought to improve trade in UK-EU market access. This piece discusses the genealogy of this reset and explores three areas for possible ‘reset’: market access, mobility and regulatory dialogue. It argues that the softening of UK-EU relations following the Windsor Framework is a necessary but not sufficient condition for an effective reset in UK-EU financial services relations and identified as regulatory dialogues that emphasise the economics, rather than politics of finance as the most likely pathway for a UK-EU reset in financial services, at least in the short term.